Comparative Evaluation of Changes in Biochemical Compounds in Tomato Plant (Solanum lycopersicum L.) Infected by Phytophthora infestans and in Response to Antifungal Plant Extracts - P. Janani; A.M. Anandakumar; M. Kabilan; L. Sowmiya; V. Raja; K. Poonkodi; E. Nagalakshmi (Archives of Current Research International, 2025)
Late blight, caused by the oomycete’s fungi Phytophthora infestans, is one of the most destructive diseases affecting tomato (Solanum lycopersicum L.) crops worldwide. Herbal-based foliar sprays derived from plant extracts offer an eco-friendly, biodegradable alternative to chemical fungicides for managing fungal diseases in crops like Solanum lycopersicum (tomato). This study examines significant alterations in carbohydrates, proteins, total free amino acids, total free fatty acids, phenolic content, and chlorophyll levels in tomato plants subjected to late blight infection and subsequent treatments with antifungal plant extracts as foliar spray. About five novel formulations using aqueous leaf extracts of Carica papaya, Lantana camara and Syzygium cumini were tested against Phytophthora infestans-infected tomato plants. By the results, it showed an increase in the level of protein content, Phenolic content and chlorophyll content. This research underscores the potential of antifungal foliar sprays in modulating biochemical pathways to bolster tomato plant defenses against late blight, offering a sustainable approach to disease management.